2022
DOI: 10.3390/app12010420
|View full text |Cite
|
Sign up to set email alerts
|

An Internet of Things (IoT)-Based Master-Slave Regionalized Intelligent LED-Light-Controlling System

Abstract: Reducing residential and industrial electricity consumption has been a goal of governments around the world. Lighting sources account for a large portion of the whole energy/power consumption. Unfortunately, most of the existing installed lighting systems are ancient and have poor energy efficiency. Today, many manufacturers have introduced light-controlling systems into the current market. However, existing light controlling systems may not be successfully applied to buildings, streets, and industrial buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Through the PIR sensor on the lamp, the energy-saving lighting in the space works in conjunction with the system counter above the office door. The LED lights in the room switch to the low-light mode together only when it is confirmed that there is no one in the office, so there is no misjudgment in the proposed system unlike for the system in [50].…”
Section: Related Workmentioning
confidence: 96%
See 4 more Smart Citations
“…Through the PIR sensor on the lamp, the energy-saving lighting in the space works in conjunction with the system counter above the office door. The LED lights in the room switch to the low-light mode together only when it is confirmed that there is no one in the office, so there is no misjudgment in the proposed system unlike for the system in [50].…”
Section: Related Workmentioning
confidence: 96%
“…Furthermore, the main idea and goal of [50] are regionalized synchronization, while the proposed system is designed for smart office lighting applications. Through the PIR sensor on the lamp, the energy-saving lighting in the space works in conjunction with the system counter above the office door.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations